Pay : employee compensation and incentive plans - Patten, Thomas Henry (New York : Free Press, 1977)
In this book the author tried to set forth the basic concepts of pay as they would apply in a contemporary large-scale industrial organization, particularly one that has both hourly and salaried employees and is involved in manufacturing, sales, and a wide range of staff- and service-supporting activities. The author has also paid heed to pertinent developments in compensation in public personnel administration where these are instructive or indicative of waves of the future.
.
Includes bibliographical references: p. 597-600 and index.
rpm 03/04/2018
Loans
Keywords: Compensation management; Remuneration -- Management aspects; United States